Definiëring in 'n aanleerderwoordeboek - Feinauer, A.E. (Lexikos, 1992)
Defining in a Learner's DictionaryBecause a learner's dictionary (in this case Basiswoordeboek vir Afrikaans) is directed at the foreign language user it stands to reason that the definitions therein will differ to a great extent from those used in a standard descriptive dictionary (for this article the Nasionale Woordeboek). This article discusses the differences in defining between these two types of dictionaries. The dissimilarity in the use of these dictionaries results in the main differences in defining: where the standard descriptive dictionary is used mainly for decoding, the learner's dictionary is also used for encoding of text. Therefore the definiens should be as unambiguous and user-friendly as possible. The ways in which this could be achieved are described, such as the use of full sentences, basic vocabulary, etc.